The Object : Documents of Contemporary Art. - Hudek, Antony; Appadurai, Arjun; Beveridge, Karl; Brown, Bill; Burn, Ian; Burnham, Jack; Dorfles, Gillo; Gullar, Ferreira; Harrison, Charles; Herkenhoff, Paulo; Iles, Chrissie; Konaté, Yakouba; et al. (London : Whitechapel, 2014)
Absalon ; Art in Ruins ; Iain Baxter ; Louise Bourgeois ; Marcel Broodthaers, Lygia Clark ; Claude Closky ; Brian D. Collier ; Jimmie Durham ; Fiaschli & Weiss . General Idea ; Izsa Genzken ; Gruppe Geflecht ; Eva Hesse ; Mike kelley ; John Latham ; Sherrie Levine ; Allan McCollum ; Gustav Metzger ; Hélio Oiticica ; Gabriel Orozco ; Katrina palmer ; Adrian Piper ; Falke Pisano ; Issa Samb ; Gregor Schneider ; Kenneth Snelson ; Song Dong ; Josef Strau ; Alina Szapocznikow ; Joëlle Tuerlinckx , 2ric Watier ; Erwin Wurm
Het ding, relatie object subject
boek